Determinants of Regional Economic Growth in Three Priority Areas of East Java Province: Policy Implication for Socio-Economic Recovery Post-Covid-19 Era - Fatimah Khoirun Nisa; Sulaeman Sulaeman (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
ABSTRACTRegional economic growth is important indicators of social economy in three priority areas of East Java Province, namely: (a) Gerbangkertosusila, (b) Bromo Tengger Semeru, (c) Selingkar Wilis and Lintas Selatan. The main objectives are: First, to analyze the main determinants of regional economic growth in the three priority areas of East Java in Indonesia; Second, to discuss how much its contribution to regional economic growth; Last, to present the policy recommendations for supporting social and economic recovery during and after the Covid-19 outbreak in East Java. This study uses an econometric approach, namely: Panel VECM or Vector Error Correction Model with Impulse-Response Function (IRF) and Forcast Error Variance Decompositions (FEVD). The findings are: (1) The main determinants of the regional economic growth model in the priority areas of East Java province are the poverty level factor, health factor, education factor, and unemployment factor, and also the regional economic growth factor in the previous period, and (2) The empirical results are expected to contribute to formulating policies for provincial and regional governments, especially policies that support social-economic recovery during and after the Covid-19 pandemic in three priority areas of East Java Province.Keywords: Regional Economic Growth, Social and Economic Recovery, Covid-19, Three Priority Areas; East JavaABSTRAKPertumbuhan ekonomi daerah merupakan indikator penting ekonomi kerakyatan di tiga wilayah prioritas Provinsi Jawa Timur, yaitu: (a) Gerbangkertosusila; (b) Bromo Tengger Semeru, dan (c) Selingkar Wilis dan Lintas Selatan. Tujuan utamanya adalah: Pertama, menganalisis determinan utama pertumbuhan ekonomi ragional di tiga wilayah prioritas Jawa Timur di Indonesia; Kedua, membahas seberapa besar kontribusinya terhadap pertumbuhan ekonomi regional; Terakhir, menyampaikan rekomendasi kebijakan untuk mendukung pemulihan sosial dan ekonomi selama dan setelah wabah Covid-19 di Jawa Timur. Penelitian ini menggunakan pendekatan ekonometrika yakni: Panel VECM (Vector Error Correction Model) with Impulse-Response Function (IRF) dan Forcast Error Variance Decompositions (FEVD). Temuan penelitian adalah: (1) Faktor penentu utama model pertumbuhan ekonomi daerah di daerah prioritas Provinsi Jawa Timur adalah faktor tingkat kemiskinan, faktor kesehatan, faktor pendidikan, dan faktor pengangguran, serta faktor pertumbuhan ekonomi regional pada tahun sebelumnya, dan (2) Hasil empiris tersebut diharapkan dapat berkontribusi dalam perumusan kebijakan bagi pemerintah provinsi dan daerah, khususnya kebijakan yang mendukung pemulihan sosial dan ekonomi selama dan setelah pandemi Covid-19 di tiga wilayah prioritas Provinsi Jawa Timur.Kata Kunci: Pertumbuhan Ekonomi Regional; Pemulihan Ekonomi Sosial; Covid-19; Tiga Kawasan Prioritas; Jawa Timur